Research for Impact of Discharge on Continuously Treating Micro-polluted Water by Electrocoagulation - JIAO Yueteng; GU Zhenghua; GU Qiaoya; SHENG Jiaoying; GAO Zhu (Renmin Zhujiang)
Purification and utilization of micro-polluted water like rainwater will be an effective way to solve the problems of water shortage.As a low-cost,high-efficiency wastewater treatment technology with a wide range of prospects,electrocoagulation has been proved to have a significant effect in treatment of heavily polluted wastewater such as industrial wastewater and domestic sewage.However,there are currently few studies on purification of micro-polluted water by electrocoagulation.Compared with batch treatment,continuous electrochemical treatment is simpler and faster,and large in treatment capacity,without human intervention.This paper discusses the impact of discharge on the continuous treatment results by electrocoagulation based on the experimental investigation of electrocoagulation test of river water.The results show that the discharge has a significant impact on the continuous treatment of micro-polluted water by electrocoagulation.There is a suitable discharge value,but the law is not obvious.Under the condition of the current density of 14.79 A/m2,and the plate distance of 1.5 cm,the discharge is about 2.0 mL/s,and after 3-hours reaction,the chroma removal rate of polluted water is 48.88%,the turbidity removal rate is 73.17%,the removal rate of suspended solids is 58.06%,the removal rate of COD is 35.00%,and the removal rate of total phosphorus is 51.22%.Furthermore,the pH of treated water rises slightly,and its conductivity decreases a little.Therefore,it is feasible to continuously purify micro-polluted water by electrocoagulation.